Impact of Social Media on Society: Understanding the Impact of Social Media on Human Health Care (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Social media is playing an important role in transmission of the information. It is an internet-based technique. People not only share their ideas or information, but also do serious discussions regarding human health care on social media. It provides an interface for the interaction of users and the service providers. The social media includes skype, whatsapp, twitter, facebook, youtube and personal blogs. There are about 2.46 billion users of social media worldwide during 2017, it is estimated that 12 rise will occur by 2019. Whereas, in India 28 of the population is using internet, out of which 10 are active on social media. There are many online websites providing information on education and health. The impact of our online habits may have effect on physical as well as mental health and behavior activities that can have potential health care challenges.